DEVELOPMENT, ANALYSIS, AND DEMONSTRATION OF TRANSACTIVE ENERGY MARKET MECHANISMS FOR DECENTRALIZED COORDINATION OF ENERGY RESOURCES WITHIN CLUSTER OF SUSTAINABLE GRID-INTERACTIVE BUILDINGS - ROHIT CHANDRA (2021)
Ph.D